Inverse kinematics of a 10 DOF modular hyper-redundant robot resorting to exhaustive and error-optimization methods: a comparative study - Sáenz Espinoza, Mario (2014)
This paper describes and compares several approaches applied to compute the inverse kinematics of a 10 degrees of freedom hyper-redundant robot. The proposed approaches are based on an exhaustive method and several erroroptimization algorithms. The algorithms’ performance was evaluated based on two criteria: computing time and final actuator positioning error. The mentioned hyper-redundant robot was projected to be used in biomedical applications.